A study of interval breast cancer within the NHS breast screening programme. Issue 2 (1st February 2000) - Cowan, W K; Angus, B; Gray, J C; Lunt, L G; Al-Tamimi, S Ramedan
Abstract : Aim —To define the biological nature and malignant potential of interval cancers presenting to a breast unit within the NHS breast screening programme. Methods —112 interval cancers were compared with matched, screen detected and symptomatic cancers in terms of their radiographic, histopathological, and immunohistochemical features. Results —Interval cancers, strictly defined, showed no characteristic radiographic pattern. In terms of size, vascular invasion, lymph node status, and prognosis they were intermediate between screen detected and symptomatic cancers. Within the interval cancers there was an excess of grade 1 and grade 3 tumours, and lesions with a high Ki67 index but immunohistochemistry otherwise failed to discriminate between the three groups. Inclusion of data from false negative "interval cancers" did not significantly alter the results. Conclusions —Interval cancers are more aggressive than screen detected cancers but in general less aggressive than symptomatic cancers. However, within a heterogeneous group, occasional interval cancers are exceptionally malignant.